Coping strategies and quality of life in schizophrenia: cross-sectional study - Holubova, Michaela; Prasko, Jan; Hruby, Radovan; Kamaradova, Dana; Ociskova, Marie; Latalova, Klara; Grambal, Ales (Neuropsychiatric disease and treatment, 2015)
BACKGROUND: The modern psychiatric view of schizophrenia spectrum disorders and their treatment has led to an increasing focus on coping strategies and the quality of life of these patients. In the present study, the authors examined the relationship between demographic data, the severity of symptoms, coping strategies, and the quality of life in psychotic patients. It is important to study the inner experience and striving of these individuals as it has been linked to their well-being and treatment adherence. METHODS: Psychiatric outpatients who met International Classification of Diseases, Tenth Revision criteria for a psychotic disorder (schizophrenia, schizoaffective disorder, or delusional disorder) were recruited in the study. Questionnaires measuring the coping strategies (The Stress Coping Style Questionnaire [SVF-78]), the quality of life (Quality of Life Satisfaction and Enjoyment Questionnaire [Q-LES-Q]), and symptom severity (objective and subjective Clinical Global Impression - objCGI; subjCGI) were assessed. The data were analyzed using one-way analysis of variance, Mann-Whitney U test, Pearson and Spearman correlation coefficients, and multiple regression analysis. RESULTS: A total of 109 psychotic patients were included in the study. The quality of life was significantly related to both the positive and negative coping strategies. The severity of disorder was highly negatively correlated with the quality of life score. The results of multiple stepwise regression analysis using the quality of life as a dependent variable showed that symptom severity (subjCGI, difference between subjCGI, and objCGI), negative coping strategies, positive coping strategies, and the difference between positive and negative coping strategies explain more than half variance. CONCLUSION: Our study suggests the importance of utilizing the positive coping strategies in improving the quality of life in patients with psychotic disorders.
Keywords: quality of life; coping strategies; psychotic disorders; severity of the disorder; schizophrenia